Effect of Problem-Based Learning Model and Motivation toward Learning Outcomes on Network Routing - Kurnia Dwi Ariyanti; Aye Aye Mon; Ekohariadi Ekohariadi; Lilik Anifah (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
This study explored the effect of problem-based learning and motivation toward learning outcomes of the subject of computer routing network. Computer routing network is part of the subject of computer network design in a computer network engineering class. The purpose of this study was to examine the difference in learning outcomes between students treated with the problems based learning model and treated with direct learning model by considering students’ learning motivation. This study was categorized as quasi-experimental designed with a factorial experimental design. The sampling technique used purpose-sampling. The data were analyzed using a two-way Anava method. The results of the study showed that (1) the learning outcomes of students in the subject of routing network with problem-based learning model was better than the student treated with direct instruction learning, (2) based on the learning outcomes in the subject of routing network, a group of students with high motivation was better, and (3) there is an interaction between the application of problem-based-learning model and motivation to the students learning outcomes.